Biomass and lipid production by microalgal strain isolated from freshwater lake in Kuantan, Pahang in response to nutrient stress and its phycoremediation potential - Mohd Ashaari, Mardiana; Md Azmi, Fatin Hamimi; Ismail, Nur Faiqah; Azizan, Nur Inani; Abdul Halim, Khairul Bariyyah (IIUM Press, 2024)
Microalgae is a potential feedstock for biofuel production due to high biomass production and lipid content. It is a treatment agent for pollution as it can remove excess nutrient from water using a technique called phycoremediation. In this study, freshwater microalgae are isolated and purified with the aim to screen for high biomass yield and lipid content. The microalgal strain Scenedesmus sp. and Oscillatoria sp. were successfully isolated with preliminary screening of biomass yield of 0.0502 ± 0.005 g dwt L-1 by Oscillatoria sp. compared to the yield of Scenedesmus sp. which was 0.0873 ± 0.004 g dwt L-1. Scenedesmus sp. showed the high value of lipid content which was 87% while Oscillatoria sp. constitutes 49% of lipid content. The conditions of nutrient stress or starvation particularly for nitrate and phosphate were established to determine whether the biomass yield and lipid content of Scenedesmus sp. could be further increased but it was proved to be vice versa. This study has able to find potential locally isolated candidate for biofuel production with the additional potential in remediation of pollutants such as nitrate and phosphate and can be further manipulated to increase the biomass yield and lipid content.